Atmospheric particle number size distribution and size-dependent formation rate and growth rate of neutral and charged new particles at a coastal site of eastern China. (1st February 2022) - Huang, Xiangpeng; Ge, Xinlei; Liu, Dan; Tong, Lei; Nie, Dongyang; Shen, Fuzhen; Yang, Mengrong; Wu, Yangzhou; Xiao, Hang; Yu, Huan
Abstract: Coastal new particle formation (NPF) may be complicated due to the influence of both continental and marine air masses. Here we presented the result of particle number size distribution and NPF event measurements at a coastal industrial park of eastern China from 2018 to 2019. The highest nucleation-mode particle number concentration (daytime maximum: 4.9 × 10 3 cm −3 ) and NPF frequency (8% of the observation days) were observed in the continental-marine air masses that originated from North China Plain and traveled along the coastline before arriving at the coastal site. The formation rates of 2 nm particles ( J 2 ) at this coastal site are similar to those reported in the urban environments around the world, probably due to the influence of local industrial emission. Ion to total particle number concentration ratios in 2–7 nm and 7–20 nm were 1.5% and 12%, respectively, during the NPF periods. Neutral new particle formation pathway thus dominated over ion-mediated pathway at this coastal site. Our observation also showed that number concentration and formation rate of neutral new particles decreased monotonically with particle size, while those of charged new particles increased with particle size. Such difference points to additional formation and loss mechanisms of charged particles, such as ion-aerosol attachment and ion-ion recombination in the atmosphere. The behavior of appearance time-based growth rates, however, are similar for neutral and charged particles. Highlights: Continental-marine air mass was favorable for new particle formation at the coastal site. Formation rate of neutral particles decreased with particle size, while that of charged particles increased with size. Neutral pathway dominated over ion-mediated pathway during the coastal NPF events.